ANALISIS PEMANFAATAN PLATFORM MERDEKA BELAJAR PADA MATA PELAJARAN TEKNIK KOMPUTER JARINGAN DAN TELEKOMUNIKASI - Suwaji, Rudy Pangestu (EduTeach : Jurnal Edukasi dan Teknologi Pembelajaran, 2024)
This research aims to quantitatively analyze the utilization of the Merdeka Belajar Platform at SMKN 6 Pekanbaru, specifically focusing on the subject of Computer Network and Telecommunication Engineering. The Merdeka Belajar Platform is a government initiative aimed at enhancing access and effectiveness in learning in the digital era. The research focuses on quantifying the extent to which teachers and students at SMKN 6 Pekanbaru utilize the platform in the learning process and identifying quantifiable challenges and opportunities that arise during its implementation. The research adopts a quantitative approach with data collection techniques including statistical analysis of observations, structured interviews, and document analysis. The expected outcomes of the study aim to provide quantitative insights into the effectiveness of utilizing the Merdeka Belajar. The findings' implications can serve as a quantitative basis for further improvement and development in the implementation of e-learning platforms in vocational high school Kata kunci: Merdeka Learning Platform, Teknik Komputer Jaringan dan Telekomunikasi, SMKN 6 Pekanbaru, Pembelajaran Digital, Evaluasi Pemanfaatan